GAMBARAN SISA MAKANAN DAN MUTU MAKANAN YANG DISEDIAKAN INSTALASI GIZI RUMAH SAKIT UMUM PUSAT DR. KARIADI SEMARANG - PURUHITA, NIKEN; HAGNYONOWATI, HAGNYONOWATI; ADIANTO, SIGIT; MURBAWANI, ETISA ADI; ARDIARIA, MARTHA (JNH (Journal of Nutrition and Health), 2013)
Background: The therapeutic outcome strongly depends on the nutrition care. Nutrition department is responsible on in-patient?s nutrients fulfillment. A comprehensive nutrition care comprised of planning, providing the diet, food processing and serving must be conducted by this department. Previous study shows 50% in-patient did not complete the meal and 75% complained the meal served. This condition leads to nutrients inadequacy and hence the malnutrition in hospital. No similar study is being conducted in dr. Kariadi Hospital Semarang. Method: A cross sectional descriptive study were being conducted for 11 days. The responden size is 30 from several wards in Dr.Kariadi Hospital who received a normal meal. The datas collected was a primary data trough direct oservation and interview using a questionairre. Penelitian ini merupakan penelitian deskriptif yang dilakukan selama 11 hari dengan pendekatan Result: Food residues ? 75% for animal-based was 9%, plant-based 3% dand vegetables 18% according to the Comstock method. From one single menu cycle, most of all considered to be good in taste and look. But there were still a few serves, animal-based (7 serves), plant-based 94 serves), and vegetables (6 serves) cosidered to be bad in taste and look for  ? 50% respondent. Conclusion: Most food residue derives from vegetables and animal-based so it needs a better and more variation in its processing. Key word:Food residue, Comstock